Sewing shirts with injured fingers and tears: exploring the experience of female garment workers health problems in Bangladesh - Sadika Akhter; Shannon Rutherford; Cordia Chu (BMC, 2019)
Abstract Background The ready-made garment industry in Bangladesh not only contributes to the nation's economic development, but has created income opportunities for women, benefiting their whole family. However, these benefits come at considerable cost to the women. This research examines how the work environment and gendered family role in this conservative society affect the health of the female industrial workers. Methods A qualitative study employed in-depth interviews (n-20) and focus group discussions with female garment workers (n-4) in two cities of Dhaka district. Further, key informant interviews (n = 4) with factory doctors, along with eight workplace observations were conducted to explore the lived experience of female workers' health issues. Interview transcripts were coded in Atlas-ti, 5.2. The data were analysed using thematic analysis approach. The themes are illustrated with case narratives. Results The female workers reported that their work has led to back and joint pain, continuous headache, eye pain and difficulty in breathing associated with inhaling fabric dust. Inadequate lighting, constantly sitting in one position without back rest and continuous noise from hundreds of machines makes them feel permanently tired. Further, the female workers reported that working in the factory and meeting the expectations of the families at home has doubled their workload. The doctors indicated that the physical work environment, their low job status and the nature of the job affect the health of female workers. Conclusion This study found that female workers in the ready-made garment industry face a high risk of health problems. Both government and non-government organizations need to be better involved in designing interventions targeting these women, to protect them from such health risks. In addition, recognition by the whole society of the important role the women play in the economy is needed, so that support by both family and society can be improved.